Implementation of Learning Videos As an Effort to Improve Grade V Students' Understanding in the Course of Creed and Morals - Al Afif Hazmar; Nur Asiah; Mohd Aizul bin Yaakob; Heri Khoiruddin (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This research was motivated by students' low understanding of the material on faith and morals. Learning is still conducted conventionally without engaging media. This makes students less active and easily bored. Therefore, video media is used to improve their understanding. This study aims to improve student understanding using instructional videos. This study is a non-participant Classroom Action Research (CAR). The author acts as an observer, while the teacher acts as the implementer. The study was conducted in two cycles in class V of MI Ilman Nafian. The research results showed an increase in student understanding from cycle I to cycle II. In cycle II, students were more active and their post-test scores improved. The gradual video and discussion strategies proved effective. Students were also more focused when watching and completing the worksheets. In conclusion, video media can improve students' understanding of faith and morals. Videos make learning more engaging and easier to understand. Teachers are advised to use media that suits the characteristics of their students. Appropriate media encourages more active and meaningful learning.